2009
DOI: 10.1136/jech.2008.082461
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the demerit point system on road traffic accident mortality in Spain

Abstract: Implementation of the DPS in Spain has led to a significant reduction in the number of traffic accident deaths in the context of a downward trend after the implementation of the 2004 measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 6 publications
2
17
0
2
Order By: Relevance
“…Finally, the number of traffic injuries in Spain had already decreased substantially after the prioritization of road safety there in 2004. 13 In Spain, a previous study had observed a 14.5% reduction in overall fatalities on nonurban roads, 9 a reduction similar to the10% and 12% reductions, respectively, in the numbers of men and women killed or seriously injured, as observed in the present study.…”
Section: Comparison With Previous Studiessupporting
confidence: 73%
See 2 more Smart Citations
“…Finally, the number of traffic injuries in Spain had already decreased substantially after the prioritization of road safety there in 2004. 13 In Spain, a previous study had observed a 14.5% reduction in overall fatalities on nonurban roads, 9 a reduction similar to the10% and 12% reductions, respectively, in the numbers of men and women killed or seriously injured, as observed in the present study.…”
Section: Comparison With Previous Studiessupporting
confidence: 73%
“…In Spain, the effectiveness of the PPS has been assessed only for overall numbers of fatalities on nonurban roads. 9 In addition, none of those studies have analyzed changes in risk among drivers, who are the main target of the PPS. Our objective was to assess the effectiveness of the PPS in reducing the number of drivers involved in injury collisions (i.e., traffic collisions resulting in injury) and the number of people injured in traffic collisions in Spain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that DDTI joinpoints match with the introduction of relevant traffic safety regulations might suggest, although never prove, a causal link, which could be further investigated with an adequate methodology. In any case, our results for global DDTI rates are consistent with previous analytical studies (Novoa et al, 2010a(Novoa et al, , 2011Pulido et al, 2010). An analytic approach could have been adopted, establishing previous causal hypotheses about the positive effects of a specific regulation or intervention and looking to see if a joinpoint appears shortly before or coincident with its introduction.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies suggest that some specific interventions, mainly focused on preventing reckless behaviours such as excessive speeding, alcohol-impaired driving (AID), or driving without helmets or seatbelts, have been effective (Brady et al, 2009;Castillo-Manzano et al, 2011;Elvik and Vaa, 2004;Fell and Voas, 2006;Goss et al, 2008;Ker and Chinnock, 2008;Liu et al, 2008;McMillan and Lapham, 2006;Novoa et al, 2009;Shults et al, 2004Shults et al, , 2009Wilson et al, 2006). Single pre-/post intervention studies -e.g., interrupted time series -are perhaps the most common designs used for this purpose (Killoran et al, 2010;Novoa et al, 2010aNovoa et al, ,b, 2011Pulido et al, 2010;Wilson et al, 2010). However, it is difficult to assess the effectiveness of specific interventions due to the intrinsic complexity of the relationship between traffic injuries, risk factors, and policies, as well as the limitations of surveillance systems (Peden et al, 2004).…”
Section: Introductionmentioning
confidence: 96%